DETERMINAN KINERJA KEUANGAN PEMERINTAH DAERAH: STUDI KASUS PADA KALIMANTAN TENGAH - Agnes Theresia Ahad; Erna Sulistyowati (Politeknik Negeri Jakarta, 2026)
This study aims to analyze factors determining local government financial performance in Central Kalimantan Province. The study was conducted across 13 regency and 1 city for the period 2020 to 2024, employing panel regression within the framework of stewardship theory. The research population encompasses all regency and city in Central Kalimantan, using a saturated sampling approach, yielding a total of 70 data observations. Panel regression analysis was conducted utilizing EViews 13 as the analytical tool, and the best-fitting model identified was the Random Effects Model. The results indicate that the financial reliance on regional funding and capital spending has a notable adverse impact on how local governments perform financially in the districts and municipalities of Central Kalimantan Province. Conversely, revenue generated locally contributes positively to the financial success of these districts and municipalities in Central Kalimantan Province Keywords: Regional Financial Dependence; Local Own- source Revenue (PAD); Capital Expenditure; and Financial Performance